Description of the 2020 NEMSIS Public-Release Research Dataset. (19th May 2023) - Ehlers, Julianne; Fisher, Benjamin; Peterson, Skyler; Dai, Mengtao; Larkin, Angela; Bradt, Lauri; Mann, N. Clay
Abstract: Background: The National Emergency Medical Services Information System (NEMSIS) is a federally funded program designed to standardize Emergency Medical Services (EMS) patient care reporting and facilitate state and national data repositories for the assessment and improvement of EMS systems of care. This manuscript characterizes the 2020 submissions to the National EMS Database, detailing the strengths and limitations associated with use of these data for public health surveillance, improving prehospital patient care, critical resource allocation, clinician safety, system quality assurance and research purposes. Methodology: Using the 2020 NEMSIS Public-Release Research Dataset (NEMSIS dataset), we evaluated the dataset completeness (i.e., presence of missing/null values), dataset content and assessed data generalizability. The analysis focused on 9-1-1 EMS activations resulting in the treatment and transport of a patient, except for out-of-hospital cardiac arrests for which all patients were included regardless of transport status. Results: In 2020, 43, 488, 767 EMS activations were reported to the National EMS Database by 12, 319 agencies serving 50 states and territories. Of the 19, 533, 036 9-1-1 EMS activations reportedly treating and transporting a patient, the majority were attended by "non-volunteer" clinicians (77%) working in a fire-based EMS agency (35%) certified to offer Advanced Life Support (ALS) Paramedic service (80%) and located in an urban area (82%). 9-1-1 call centers most often dispatched EMS for "sick person" (20%), while EMS clinicians most likely reported asthenia (7%) as the patient's primary symptom as well as the clinician's primary impression (6%), and documented "fall on same level, slip, or trip" as the most common cause of injury (37%). The NEMSIS dataset demonstrates some "missingness" and element inconsistencies, but methods may be employed to mitigate these data limitations. Conclusions: The National EMS Database is a free and publicly available resource for evaluating EMS system utilization, response, and prehospital patient care. Understanding the characteristics of the underlying dataset and known data limitations will help ensure proper analysis and reporting of research and quality metrics based on nationally standardized NEMSIS data.